The effect of fish oil supplementation on fatigue perception following submaximal exercise during the COVID-19 pandemic - Nurussyariah Hammado; Etno Setyagraha; Fadra Naufal Rannu (Journal Sport Area, 2023)
The pandemic of COVID-19 has created the "New Normal" lifestyle and limited people to performing their daily activities from home. These changes in turn affect the level of physical activities, including the intention to engage in regular exercise, in most people, subsequently putting them at risk of having negative effects due to being physically inactive. This condition may down regulate the human immune system, making it more vulnerable to various diseases. Oral supplementation of fish oil has been proposed to have benefits for decreasing pro-inflammatory markers induced by exercise. This study aimed to analyze the effect of fish oil supplementation on the degree of fatigue perception following submaximal exercise. Forty-four male college students participated in this non-equivalent pre-posttest experimental research. The participants were supplemented with 2 soft capsules of 1.5 grams of fish oil for 8 weeks. The effect of submaximal exercise was carried out by the sit-up and bleep tests, which were measured before and after 8 weeks of fish oil supplementation. The research procedure was approved by the ethics committee of the Makassar State University research institute. The results showed that there was a strong relationship between the administration of fish oil supplements and the level of fatigue perception following sit-ups and bleep tests (p values of -0.529 and -0.658, respectively) performed during the COVID-19 pandemic. This study concludes that the administration of fish oil supplementation affects the degree of fatigue perception after doing submaximal exercise, especially during the COVID-19 pandemic.